Pengembangan Website Desa sebagai Proses Digitalisasi Informasi dan Mempromosikan Potensi Desa - Noviandari, Hanifah (STAI Terpadu Yogyakarta, 2023)
Undoubtedly, the independent management of the Ngunut Village website definitely provides convenience in optimizing information services and Ngunut's promotional potential. Therefore, community service is proposed,